Berry phase in strained InSb whiskers - Druzhinin, A.; Ostrovskii, I.; Khoverko, Yu.; Liakh-Kaguy, N.; Rogacki, K. (Физика низких температур, 2018)
Strain influence on the longitudinal magnetoresistance for the n-type conductivity InSb whiskers doped by Sn to concentrations 6·10¹⁶–6·10¹⁷ сm⁻³ were studied at temperatures from 4.2 to 50 K and magnetic field up to 10 T. The Shubnikov–de Haas oscillations at low temperatures were revealed in the strained and unstrained samples with all range doping concentration. Some peaks of the longitudinal magnetoresistance split as a doublet in the InSb whiskers with doping concentration in the vicinity to metal-insulator transition. Taking into account peak splitting giant g-factor from 30 to 60 was defined for strained and unstrained samples. The magnetoresistance oscillation period of the InSb whiskers doesn’t differ under strain for all doping concentration, but Fermi energy increases and electron effective mass mс decreases and consists 0.02 m₀. Berry phase presence was also revealed in strained n-InSb whiskers that shows their transition under a strain to topological insulator phase.